The Pattern of Suicidal Cases in Sylhet Region - Rony, Md Shyful Islam; Afroze, Nusrat; Mutsuddy, Sumon; Islam, Md Shamsul; Sultana, Sharmin; Haque, Marina (Journal of Brahmanbaria Medical College, 2026)
Background: Suicide remains a major global public health concern,claiming 705000 lives per year. Understanding the pattern of suicide is crucial for effective prevention strategies. To highlight the importance of recognizing patterns for designing effective prevention strategies and intervention. Materials and methods: This retrospective study was done at Department of Forensic Medicine of Sylhet MAG Osmani medical college to analysis the pattern of suicidal cases during the study period from January 2024 to January 2025. After reviewing all postmortem report 100 cases of death were found due to suicidal cases during the study period. Results: The highest number of the victim 40 were from the age group 21 to 30 years followed by 30 from the age group of 11 to 20 years and 91 cases come from different rural areas where 64 cases were male and 36 cases were female.The commonest method was hanging (47) then poisoning (42) lastly through drowning (11). Conclusion: A deeper understanding of these patterns can inform targeted intervention, promote mental health awareness and ultimately help to reduce the incidence of suicide globally. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 22-24